2013
DOI: 10.1038/bmt.2013.44
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between histological manifestations of cord colitis syndrome with GVHD

Abstract: Cord colitis syndrome (CCS) is a recently proposed clinical entity characterized by a persistent diarrheal illness after cord blood transplantation (CBT), which is not caused by GVHD or CMV colitis. CCS is histologically characterized by chronic active colitis with granulomatous inflammation and Paneth cell metaplasia suggesting chronicity. However, the specificity of these pathological features to CCS remains to be validated. We conducted a retrospective study of 49 patients who had diarrhea and underwent dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 27 publications
0
27
1
Order By: Relevance
“…Thus, it is tempting to assume that enhanced production of RegIIIg is a natural adaptation mechanism for the dysbiosis in GVHD. Paneth cell metaplasia is also observed in the colon of GVHD patients, probably as an adaptation mechanism for Paneth cell loss and the dysbiosis [30]. We have shown that Paneth cellederived a-defensin production is markedly inhibited in GVHD that have selective bactericidal activity mostly against Gram-negative bacteria [7,31,32].…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is tempting to assume that enhanced production of RegIIIg is a natural adaptation mechanism for the dysbiosis in GVHD. Paneth cell metaplasia is also observed in the colon of GVHD patients, probably as an adaptation mechanism for Paneth cell loss and the dysbiosis [30]. We have shown that Paneth cellederived a-defensin production is markedly inhibited in GVHD that have selective bactericidal activity mostly against Gram-negative bacteria [7,31,32].…”
Section: Discussionmentioning
confidence: 95%
“…The DFCI investigators used a unique non-standard definition of GVHD that excluded GVHD in colonic biopsies showing low or rare apoptosis or any features of chronicity as described above. Subsequently, two much larger studies including controls who received cord blood and non-cord blood hematopoietic stem cell transplants showed that neither the histological features of chronicity (crypt distortion, Paneth cell metaplasia, chronic active colitis) nor granulomas were confined to cord blood recipients [73, 74]. In the study by Milano et al, all of the non-cord blood allogeneic recipients with late onset secretory diarrhea and symptoms ascribed to CCS responded to anti-GVHD treatment [73].…”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 99%
“…In the study by Milano et al, all of the non-cord blood allogeneic recipients with late onset secretory diarrhea and symptoms ascribed to CCS responded to anti-GVHD treatment [73]. The presence of granulomas with neutrophilia was more common in a Japanese study that included many cases with both GVHD and CMV [74]. These studies serve as a reminder that GVHD and infection are not mutually exclusive diagnoses and reinforce the need to use standardized histological definitions for GVHD.…”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 99%
“…Colonoscopy reveals erythematous mucosa with or without ulceration, and biopsy demonstrates chronic active colitis, frequently with associated granulomas 136 . This clinical entity remains controversial, as studies have suggested that CCS is not a histopathologically distinct disease from acute GVHD 137,138 .…”
Section: Differential Diagnosismentioning
confidence: 99%